Entre a individualização e a multiplicidade: possibilidades de rupturas com os modos de gestão e administração dos corpos infantis - Cruz, Soráia Georgina Ferreira de Paiva [UNESP] (My University, 2012)
Placing the management of childhood forms considered at risk, we discuss the operation of a welfare institution and its effects on the subjective process. Created to manage the virtues of the poor behavior of children, makes visible to the way technology features disciplinary policies: surveillance is evident of cameras, high walls, electric fences and in the eyes of educators, the penalty stands normalizing practices corrective aimed at standardization bodies, educational meetings are compared to the examination, as they produce dossiers of individual behavior, emphasizing characteristics that are considered dangerous anticipates the administration and production of docile individuals, useful, productive, applying identity models. Following the lines of knowledge and power relations that constitute this space, we used the genealogy in the analysis of discursive practices that cross society in its historical construction, the genealogy allows us to achieve these movements in the consolidation process of the government of life, and also, the deconstruction of hegemonic practices. In an attempt to escape the set, we propose the realization of artistic and cultural activities within a process of collective construction as a strategy of resistance and confrontation with the dominant logic, consolidating practices that favor the enhancement of life in its manifold possibilities.

Situando as formas de gestão da infância considerada em risco, problematizamos o funcionamento de uma instituição de assistência e seus efeitos no processo de subjetivação. Criada para gerir as virtualidades do comportamento das crianças pobres, visibiliza-se a tecnologias políticas características do modo disciplinar: a vigilância evidencia-se na presença de câmeras, muros altos, cercas elétricas e no olhar dos educadores; a sanção normalizadora se destaca nas práticas corretivas visando à normalização dos corpos; as reuniões pedagógicas podem ser comparadas ao exame, na medida em que produzem dossiês dos comportamentos individuais, ressaltando características consideradas perigosas antecipa-se a administração e produção de indivíduos dóceis, úteis, produtivos, aplicando modelos identitários. Acompanhando as linhas dos saberes e das relações de poder que constituem esse espaço, utilizamos a genealogia na análise das práticas discursivas que atravessam a sociedade em sua construção histórica; a genealogia nos permite alcançar movimentos presentes no processo de consolidação do governo da vida, e, também, a desconstrução de práticas hegemônicas. Na tentativa de escapar ao instituído, propusemos a realização de atividades artísticas e culturais dentro de um processo de construção coletiva, enquanto estratégia de resistência e enfrentamento à lógica dominante, consolidando práticas que favorecem a potencialização da vida em suas múltiplas possibilidades.
Between and individualization multiplicity: possibilities of ruptures with the ways of management and administration children bodies
Keywords: Assistance; State; Society Disciplinary; Assistência; Estado; Sociedade disciplinar